2014
DOI: 10.1158/0008-5472.can-14-0562
|View full text |Cite
|
Sign up to set email alerts
|

NQO1 Suppresses NF-κB–p300 Interaction to Regulate Inflammatory Mediators Associated with Prostate Tumorigenesis

Abstract: NADPH reductase NQO1 is needed to maintain a cellular pool of antioxidants and this enzyme may contribute to tumorigenesis, on the basis of studies in NQO1-deficient mice. In this work, we sought deeper insights into how NQO1 contributes to prostate carcinogenesis, a setting where oxidative stress and inflammation are established contributors to disease development and progression. In the TRAMP mouse model of prostate cancer, NQO1 was highly expressed in tumor cells. NQO1 silencing in prostate cancer cells inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…33). In addition, it has been reported that NQO1 suppresses NF-κB-p300 interaction to regulate inflammatory mediators associated with prostate tumorigenesis52. These studies suggested that NQO1 could act to suppress tumorigenesis in certain conditions.…”
Section: Discussionmentioning
confidence: 96%
“…33). In addition, it has been reported that NQO1 suppresses NF-κB-p300 interaction to regulate inflammatory mediators associated with prostate tumorigenesis52. These studies suggested that NQO1 could act to suppress tumorigenesis in certain conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Increased 8‐oxoG with age and in CaP has been found by different methods in tissues, urine and serum (Malins et al., 2001; Miyake et al., 2004; Kosova et al., 2014). Also, a role of NQO1 in blocking CaP progression has been recently proposed for the mouse TRAMP CaP model (Thapa et al., 2014). Furthermore, NQO1 silencing in CaP cells enhanced the levels of nuclear IKKalpha and NF‐kB while decreasing the levels of p53, leading to interactions between NF‐kB and p300 that reinforce cellular pro‐survival signalling (Thapa et al, 2014; Bouchal et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, NQO1 has positive effects on malignant cells that are already in neoplastic state 22-24, but, as a part of senescence barrier, NQO1 also exhibits anti-tumorigenicity properties during the malignant progression by which normal cells evolve to cancer cells.…”
Section: Discussionmentioning
confidence: 99%